Ответ:
Объяснение:
4)
√(x²-3x+11)-4x²+12x=11
√(x²-3x+11)-4x²+12x-44=11-44
√(x²-3x+11)-4*(x²-3x+11)=-33
Пусть √(x²-3x+11)=t≥0 ⇒
t-4t²=-33
4t²-t-33=0 D=529 √D=23
t₁=-2,75 ∉
t²=3 ⇒
√(x²-3x+11)=3
(√(x²-3x+11))²=3²
x²-3x+11=9
x²-3x+2=0 D=1
x₁=2 x₂=1.
5)
ОДЗ: x-1≠0 x≠1 2-x≠0 x≠2.
Пусть
⇒
![t-\frac{7}{t} =6\\t^{2} -6t-7=0\\D=64;\sqrt{D}=8\\ t-\frac{7}{t} =6\\t^{2} -6t-7=0\\D=64;\sqrt{D}=8\\](https://tex.z-dn.net/?f=t-%5Cfrac%7B7%7D%7Bt%7D%20%3D6%5C%5Ct%5E%7B2%7D%20-6t-7%3D0%5C%5CD%3D64%3B%5Csqrt%7BD%7D%3D8%5C%5C)
t₁=7 t₂=-1 ∉ ⇒
![\sqrt{\frac{2-x}{x-1} } =7\\(\sqrt{\frac{2-x}{x-1} } )^{2} =7^{2} \\\frac{2-x}{x-1} =49\\2-x=49*(x-1)\\2-x=49x-49\\50x=51|:51\\x=\frac{51}{50}. \sqrt{\frac{2-x}{x-1} } =7\\(\sqrt{\frac{2-x}{x-1} } )^{2} =7^{2} \\\frac{2-x}{x-1} =49\\2-x=49*(x-1)\\2-x=49x-49\\50x=51|:51\\x=\frac{51}{50}.](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B2-x%7D%7Bx-1%7D%20%7D%20%3D7%5C%5C%28%5Csqrt%7B%5Cfrac%7B2-x%7D%7Bx-1%7D%20%7D%20%29%5E%7B2%7D%20%3D7%5E%7B2%7D%20%5C%5C%5Cfrac%7B2-x%7D%7Bx-1%7D%20%3D49%5C%5C2-x%3D49%2A%28x-1%29%5C%5C2-x%3D49x-49%5C%5C50x%3D51%7C%3A51%5C%5Cx%3D%5Cfrac%7B51%7D%7B50%7D.)